2018
DOI: 10.3802/jgo.2018.29.e89
|View full text |Cite
|
Sign up to set email alerts
|

Treatment results of the second-line chemotherapy regimen for patients with low-risk gestational trophoblastic neoplasia treated with 5-day methotrexate and 5-day etoposide

Abstract: ObjectiveHighly effective chemotherapy for patients with low-risk gestational trophoblastic neoplasia (GTN) is associated with almost a 100% cure rate. However, 20%–30% of patients treated with chemotherapy need to change their regimens due to severe adverse events (SAEs) or drug resistance. We examined the treatment outcomes of second-line chemotherapy for patients with low-risk GTN.MethodsBetween 1980 and 2015, 281 patients with low-risk GTN were treated. Of these 281 patients, 178 patients were primarily tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
5
1
Order By: Relevance
“…No significant differences in cure and drug resistance rates were observed between the MTX + CF and ACT-D groups, which is inconsistent with the findings of previous studies (Osborne et al 2015;Kanno et al 2018). This may be attributed to the reduction in the adverse reactions of CF, which minimizes autoimmune responses and improves patient prognosis.…”
Section: Discussioncontrasting
confidence: 86%
“…No significant differences in cure and drug resistance rates were observed between the MTX + CF and ACT-D groups, which is inconsistent with the findings of previous studies (Osborne et al 2015;Kanno et al 2018). This may be attributed to the reduction in the adverse reactions of CF, which minimizes autoimmune responses and improves patient prognosis.…”
Section: Discussioncontrasting
confidence: 86%
“…The success of this combination therapy is due to the two drugs' complementary actions. Kanno et al (2018) reported the same result, that single MTX administration to low risk GTN patients resulted in remission failure (35 %). To overcome this condition, a second line of therapy is required; one of the combinations used is MTX and ETP for 5 days, and complete remission is achieved by 83.3 percent of the total patients who experience therapy failure using single chemotherapy.…”
Section: Discussionmentioning
confidence: 65%
“…After a single chemotherapy administration of MTX, or etoposide (ETP), the low-risk GTN achieves nearly 100 percent complete remission patients [17]. Methotrexate can effectively inhibit trophoblast cell proliferation by inhibiting DNA replication and the cell cycle in the S phase [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both defining and treating low-risk GTN remain somewhat controversial [4]. Tumor resistance is described as an increase in hCG levels or their stagnation over a 2 to 3-week period [5], although there is no internationally accepted consensus on the definition of drug resistance resulting from chemotherapy [6]. There is also no diagnostic tool available to predict chemoresistance and consequently to establish an appropriate treatment schema at the beginning of therapy.…”
Section: Discussionmentioning
confidence: 99%